From Eco-Anxiety to Climate Activism: The Moderating Role of Collective Efficacy Among Generation Z in Indonesia - Jasmila Tanjung; Sarah Armalia; Zahra Amir (HM Publisher, 2026)
Background: Escalating environmental hazards across Indonesia have transformed the climate crisis into a collective mental-health and sociological concern, yet whether ecological anxiety paralyses or mobilises young people remains contested, and Global South evidence is scarce. Objective: Drawing on the Social Identity Model of Collective Action integrated with collective-efficacy theory, this study examined whether collective efficacy moderates the eco-anxiety to climate activism relationship and whether catalytic eco-anger mediates it. Methods: A cross-sectional survey was administered to 1,500 Generation Z respondents aged 16 to 24 years recruited through public organizations in Palembang, South Sumatera, Indonesia, using validated multi-item five-point Likert scales. Analyses comprised reliability and confirmatory measurement modelling, a correlation matrix, hierarchical moderated regression with simple-slope decomposition, bootstrapped mediation, and diagnostics for common-method bias, multicollinearity, and clustering. Results: All constructs were reliable (Cronbach's alpha 0.84-0.88; McDonald's omega 0.84-0.87; composite reliability 0.84-0.87; average variance extracted 0.63-0.65) and discriminant validity was supported (heterotrait-monotrait ratios <=0.62). Common-method bias was not a threat (Harman first factor 36.96%). Collective efficacy positively predicted activism (beta = 0.39, 95% CI [0.35, 0.43], p < 0.001) and significantly moderated the eco-anxiety to activism path (interaction beta = 0.57, 95% CI [0.53, 0.60], p < 0.001; Delta-R2 = 0.32; f2 = 0.55). Simple slopes showed a crossover: eco-anxiety was associated with lower activism at low efficacy (-0.56) but higher activism at high efficacy (0.57). Catalytic eco-anger competitively mediated the association (indirect = 0.33, 95% CI [0.29, 0.38]) against a negative direct effect (-0.24). Conclusion: Collective efficacy conditions whether climate distress becomes organised activism, extending collective-action theory to the Global South and informing Indonesian youth and climate policy.